The secessionist attempt in Catalonia in the light of International Law - López Martín, Ana Gemma (2018)
The attempted secession promoted in 2017 by a part of the members of the Parliament of Catalonia raises questions of enormous interest for International Law. In the first place, regarding whether national minorities, groups or peoples have recognized in the international order a right of self-determination such as that enjoyed by peoples subject to colonial domination or by force; if the so-called right to secession-remedy has been consolidated as an international custom and if there can be other foundations for the secession of this kind of peoples, such as the democratic principle or majority theory. And second, in relation to the effectiveness of a declaration of independence and the verification of the elements that make up a State and allow confirming its creation; with compliance, in that process of creation, of international legality, and the consequent obligation, otherwise, of non-recognition of those entities arising from the violation of International Law.